Kebertahanan Angkringan pada Era New Normal di Kelurahan Sentanan, Kota Mojokerto - . Riyantono; I Gusti Putu Sudiarna; I Ketut Kaler (Department of Anthropology Udayana University, 2023)
Angkringan is one of the typical culinary delights of the people who are now increasingly enjoying themselves, including in the New Normal era. This study aims to how does it survive in the New Normal era in Mojokerto City. This study uses the Functionalism theory by Bronislaw Malinowski and the Hierarchy of Human Needs theory by Abraham Maslow that uses a qualitative research method with an ethnographic research model through observation, interviews, and literature studies. The results of the study, it was found that the background of the existence of angkringan started from the economism respons of the Wong Kulonan overseas group who lived in Mojokerto City, the angkringan business in Mojokerto City also were accustomed to opening side jobs. Which then becomes an alternative job, and the needs of the people of Mojokerto City will have a wider public space The survival strategy of angkringan in the New Normal comes from the form of angkringan business that adapts to the New Normal era with simple capital and easy operations, high consumer interest with prices that adjust in the midst of a crisis and public space.